2009
DOI: 10.1159/000232947
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach in the Surgical Management of Anterior Capsular Phimosis Syndrome

Abstract: Anterior capsular opacification and contraction syndrome is a well-recognised complication of uneventful phacoemulsification. It often results in a clinically significant reduction in vision secondary to central opacification, intraocular lens decentration and tilt. We report 3 cases of anterior capsular phimosis, which we treated using a new technique, where long, fine pointed scissors are used to cut the anterior capsule radially towards the edge of the lens optic and the edge is then grasped with capsulorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In more severe cases of CCS, YAG laser lysis cannot achieve effective treatment, and the proliferating fibrous membrane must be surgically seaparted under the anterior capsule and the adhesion of IOL edges and loops, to remove the fibrous membrane as far as possible by cutting or tearing it off. Radial cutting or direct continuous circular capsulorhexis was performed on the narrowed anterior capsular opening to remove the fibrous membrane, and there was no recurrence during postoperative follow-up [40]. Yeh et al [41] proposed to use an anterior vitrectomy to cut the shrunk anterior capsular opening to remove the subcapsular fibrous membrane and residual lens epithelial cells, which can reduce the chance of radial tear of the suspensory ligament and secondary IOL eccentricity.…”
Section: Discussionmentioning
confidence: 99%
“…In more severe cases of CCS, YAG laser lysis cannot achieve effective treatment, and the proliferating fibrous membrane must be surgically seaparted under the anterior capsule and the adhesion of IOL edges and loops, to remove the fibrous membrane as far as possible by cutting or tearing it off. Radial cutting or direct continuous circular capsulorhexis was performed on the narrowed anterior capsular opening to remove the fibrous membrane, and there was no recurrence during postoperative follow-up [40]. Yeh et al [41] proposed to use an anterior vitrectomy to cut the shrunk anterior capsular opening to remove the subcapsular fibrous membrane and residual lens epithelial cells, which can reduce the chance of radial tear of the suspensory ligament and secondary IOL eccentricity.…”
Section: Discussionmentioning
confidence: 99%
“…Nd:YAG laser anterior capsulotomy is the most frequent method of treatment and provides a relatively quick and painless solution for the patient [ 12 ]. However, potential drawbacks of this approach have been reported and include delayed dislocation of the IOL [ 13 ] and an increased risk for inflammation and recurrence due to cellular debris [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The more traditional method involves surgical peeling in cases of thick and fibrotic anterior capsule [ 15 ]. Using long, straight, and pointed scissors to cut the fibrotic membrane from the visual access has also been proposed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nd:YAG laser anterior capsulotomy has been proposed as a treatment option 7 ; however, capsular debris loosened by this method may enhance the risk for inflammation and recurrences. 8 Moreover, delayed dislocation of the IOL in the ciliary sulcus has been reported after Nd:YAG laser capsulotomy in cases of ACC caused by extension of the radial relieving incision to the periphery. 9 Hayashi et al 10 have shown use of Nd:YAG laser for radial anterior capsule relaxing incisions helps in preventing corneal endothelial damage more than the circular pattern.…”
Section: Discussionmentioning
confidence: 99%